A Nitrogen Molecular Sensing System, Comprised of the ALLANTOINASE and UREIDE PERMEASE 1 Genes, Can Be Used to Monitor N Status in Rice - Lee, Dong-Keun; Redillas, Mark C. F. R.; Jung, Harin; Choi, Seowon; Kim, Youn Shic; Kim, Ju-Kon (Frontiers in Plant Science, 2018)
Nitrogen (N) is an essential nutrient for plant growth and development, but its concentration in the soil is often insufficient for optimal crop production. Consequently, improving N utilization in crops is considered as a major target in agricultural biotechnology. However, much remains to be learnt about crop N metabolism for application. In this study, we have developed a molecular sensor system to monitor the N status in rice (Oryza sativa). We first examined the role of the ureide, allantoin, which is catabolized into allantoin-derived metabolites and used as an N source under low N conditions. The expression levels of two genes involved in ureide metabolism, ALLANTOINASE (OsALN) and UREIDE PERMEASE 1 (OsUPS1), were highly responsive to the N status. OsALN was rapidly up-regulated under low N conditions, whereas OsUPS1 was up-regulated under high N conditions. Taking advantage of the responses of these two genes to N status, we generated transgenic rice plants harboring the molecular N sensors, proALN::ALN-LUC2 and proUPS1::UPS1-LUC2, comprising the gene promoters driving expression of the luciferase reporter. We observed that expression of the transgenes mimicked transcriptional regulation of the endogenous OsALN and OsUPS1 genes in response to exogenous N status. Importantly, the molecular N sensors showed similar levels of specificity to nitrate and ammonium, from which we infer their sensing abilities. Transgenic rice plants expressing the proUPS1::UPS1-LUC2 sensor showed strong luminescence under high exogenous N conditions (> 1 mM), whereas transgenic plants expressing the proALN::ALN-LUC2 sensor showed strong luminescence under low exogenous N conditions (< 0.1 mM). High exogenous N (> 1 mM) substantially increased internal ammonium and nitrate levels, whereas low exogenous N (< 0.1 mM ) had no effect on internal ammonium and nitrate levels, indicating the luminescence signals of molecular sensors reflect internal N status in rice. Thus, proALN::ALN-LUC2 and proUPS1::UPS1-LUC2 represent N molecular sensors that operate over a physiological and developmental range in rice.